Histone acetyltransferase activity of MOF is required for MLL-AF9 leukemogenesis - Valerio, Daria G. (Cancer Res, 2017)
Chromatin-based mechanisms offer therapeutic targets in acute myeloid leukemia (AML) that are of great current interest. In this study, we conducted an RNAi-based screen to identify druggable chromatin regulator-based targets in leukemias marked by oncogenic rearrangements of the MLL gene. In this manner, we discovered the H4K16 histone acetyltransferase (HAT) MOF to be important for leukemia cell growth. Conditional deletion of Mof in a mouse model of MLL-AF9-driven leukemogenesis reduced tumor burden and prolonged host survival. RNA sequencing showed an expected downregulation of genes within DNA damage repair pathways that are controlled by MOF, as correlated with a significant increase in yH2AX nuclear foci in Mof-deficient MLL-AF9 tumor cells. In parallel, Mof loss also impaired global H4K16 acetylation in the tumor cell genome. Rescue experiments with catalytically inactive mutants of MOF showed that its enzymatic activity was required to maintain cancer pathogenicity. In support of the role of MOF in sustaining H4K16 acetylation, a small molecule inhibitor of the HAT component MYST blocked the growth of both murine and human MLL-AF9 leukemia cell lines. Furthermore Mof inactivation suppressed leukemia development in a NUP98-HOXA9 driven AML model. Taken together, our results establish that the HAT activity of MOF is required to sustain MLL-AF9 leukemia and may be important for multiple AML subtypes. Blocking this activity is sufficient to stimulate DNA damage, offering a rationale to pursue MOF inhibitors as a targeted approach to treat MLL-rearranged leukemias.